1983
DOI: 10.1136/jmg.20.5.321
|View full text |Cite
|
Sign up to set email alerts
|

The genetic control of sparteine and debrisoquine metabolism in man with new methods of analysing bimodal distributions.

Abstract: SUMMARY Debrisoquine and sparteine tests were carried out in 215 random white British subjects. There is a high degree of correlation between the urinary 'metabolic ratios' of the two drugs. New A polymorphism has also been described for the metabolism of sparteine, an alkaloid which has been used as an anti-arrhythmic and oxytocic drug. One phenotype with a frequency of 0-05 in the German population was unable to metabolise the compound. The other phenotype produced two substances thought to result from N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 7 publications
0
35
0
Order By: Relevance
“…The metabolic ratio (MR) was calculated by dividing the % of debrisoquine excreted by the % of the 4-hydroxy metabolite excreted in urine. Poor metabolizers are usually assigned a MR > 12.6 (Evans et al, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…The metabolic ratio (MR) was calculated by dividing the % of debrisoquine excreted by the % of the 4-hydroxy metabolite excreted in urine. Poor metabolizers are usually assigned a MR > 12.6 (Evans et al, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…However, assessment of sparteine oxidation based on the peak area MR cannot distinguish the two genotypes within the dominant phenotype (Eichelbaum et al, 1979;Evans et al, 1983). Combined family and population data have indicated that sparteine metabolism is impaired in heterozygotes compared with homozygous dominants (Evans et al, 1983 The aim of the present study was to examine the urinary excretion pattern of sparteine and dehydrosparteines in the three genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, two phenotypes are clearly defined: poor metabolizers (PM), who are homozygous for a recessive allele, and an extensive metabolizer (EM) phenotype comprising both heterozygotes and homozygous dominants (Eichelbaum et al, 1979;Evans et al, 1983). Earlier studies demonstrated coregulation of sparteine and debrisoquine oxidation (Eichelbaum et al, 1982;Inaba et al, 1983) but conflicting data have recently appeared (Evans et al, 1983;Eichelbaum & Woolhouse, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations